Test The Activity Of A Mouthwash Preparation From The Extract Senggani Leaf Ethanol (Melastoma Malabatricum l.) Against The Fungi Candida Albicans - Auliafendri, Novycha; Gultom, Roby Pahala Januario; Syari, Dina Maya; Samosir, Sri Rezeki (SEAN Institute, 2023)
The Candida albicans fungus is one of the factors that causes canker sores. Several researchers have proven that senggani leaves (Melastoma malabatricum L) have antifungal activity. The ethanol extract of senggani leaves is made by maceration. Formulated in mouthwash preparations with concentrations of 2%, 4% and 6%, then tested for antifungal activity against Candida albicans. The results of the antifungal activity test of the ethanol extract of senggani leaves obtained a Minimum Inhibition concentration at a concentration of 2%. The results of the antifungal activity of mouthwash preparations showed an average zone of inhibition. -average at a concentration of 2% 12.8 mm; 4% 13.4 mm and 6% 16.6 mm. Mouthwash preparations using ethanol extract of senggani leaves have been proven to have antifungal activity against Candida albicans which causes canker sores.